Raising Awareness About Breast Milk Composition Among Women in Latvia - Aumeistere, Liva; Zavadska, Dace (Journal of Breastfeeding Biology, 2016)
Background: Breast milk is the ideal food source that contains all components an infant needs. Infants are at risk of receiving possible pollutants and high levels of trans fatty acids through breast milk that may affect their cardiovascular health and cognitive development. Statistics indicate that the proportion of children who are breastfed up to one year of age shows an annual increase in Latvia. Objectives: 1. To review studies conducted among the Latvian population regarding breast milk composition. 2.  To evaluate the necessary future studies emphasizing the importance of the trans fatty acid content in a mother’s diet and correspondingly in breast milk and taking into consideration the new changes in Latvian legislation setting the maximum trans fat content in foodstuffs. Conclusions: There is very little research done about the human milk composition in Latvia that could be referable to a general population. It is known that the exposure of breast milk to persistent organic pollutants in Latvia corresponds to the lowest levels detected in the European countries and is not a cause of health disorders. Taking into consideration the adverse effect trans fatty acids have on human’s health regardless of the age, consumption should be as low as possible. Latvia has become the latest European Union country to set the maximum amount of trans fats in foodstuffs, yet there is no information about trans fatty acids content in human milk among women in Latvia. This problem needs to be addressed and set in motion. Therefore, it would be a novel idea to study if the TFA content also declines in milk among Latvian women after the introduction of the new legislation.
Keywords: Breastfeeding; Human milk composition; Contaminants; Diet; Persistent organic pollutants; Trans fatty acids; Latvia.